Kebijakan Makanan Bergizi Gratis: Analisis Ekonomi Politik dan Dampaknya terhadap Kesejahteraan Masyarakat Studi Kasus: SMP Negeri 4 Tanjungpinang - Nissa, Afrija Khoirun; Candra, Mellyana; Humairoh, Tisya; Gusyuliandari, Serli (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research analyses the free nutritious food policy (MBG) from a political economy perspective and its impact on community welfare through a case study at SMP Negeri 4 Kota Tanjungpinang. The MBG programme is a government initiative to address nutritional problems in vulnerable groups such as school children, toddlers, and pregnant and lactating mothers. Using a qualitative approach and literature review method, this research describes how this policy is formulated, implemented, and evaluated in the context of an archipelago that has its own logistical and socioeconomic challenges. The results show that the MBG programme has had a positive impact on the nutritional status, educational participation, and household economy of the community. However, the programme also faces fiscal challenges and criticism of the country’s budget priorities. The study recommends the importance of collaboration between the government, private sector, and civil society and the need for adaptive policies to ensure the sustainability and effectiveness of the programme.